Factors Influencing Black Males' Preparation for College and Success in STEM Majors: A Mixed Methods Study. - STRAYHORN, TERRELL L. (Western Journal of Black Studies)
This paper was designed to amplify a growing body of research that implicates minority male identity and interest in science and math learning and preparation for STEM careers. Specifically, this paper draws on both quantitative and qualitative data to examine factors influencing Black Males 'college readiness and success in STEM. Blending sociological theories on gender socialization and racialized campus environments, the author identifies several major factors ranging from pre-college STEM self-efficacy to concerted cultivation of Black boy s initial interest and sense of belonging in STEM. Survey data and illustrative quotes from interview participants demonstrate the relevance and significance of these findings and non-cognitive predictors of academic success. Implications for future policy, practice, and research are highlighted.